The optimal structure optimal insurance network in China - Ming Liu, Ming (Advances in Social Sciences Research Journal, 2022)
As an integral part of the economic network, insurance institutions and other institutions not only have equity and creditor’s rights relationships, but also, as risk management departments in the economic network, there is a risk exchange network constructed with reinsurance relationships. At the beginning of this paper, we discuss the external and internal risk spread relationship of insurance institutions. Subsequently, using Kanno’s(2014) insurance network model analysze the characteristics of China’s reinsurance market and its structure.